Breast milk production following Enhanced Recovery After Caesarean Section (ERACS) delivery: An evaluation study - Sodiq Kamal; Tri Hastuti Budiningsih; Robiul Fitri Masitoh; Novi Kurniawan (Journal of Holistic Nursing Science, 2023)
Sectio Caesarea delivery using the ERACS method is suspected of affecting milk production. Some researchers show results with varied parameters and inconsistent results. This study aims to determine the effect of various combinations of anesthetic drugs on breast milk production. This research is a descriptive correlation study with a cross-sectional approach with medical record documents as the data source. The sample in this study was 60 mothers who delivered by sectio caesarea at Aisyiyah Muntilan Hospital in July-October 2022. A total of 30 patients received a combination of anesthetic drugs 1 in topical and morphine, and 30 received a combination of anesthetic 2 in the form of vopicain, fentanyl, and dexmedetomidine. The results showed no difference in milk production in the patient group with combination 1 and 2 anesthetic drugs (p-value 0,000 with α: 0.05). This study concluded a difference in milk production in patients who received the anesthetic combination of vopicain, fentanyl, and dexmedetomidine and the combination of vopicain and morphine. Keywords: maternity care; ERACS; child Care; post partum care; mother and child health